LACCASE PRODUCTION BY Marasmius sp. FROM OIL PALM EMPTY FRUIT BUNCH (OPEFB) USING TRICKLE-BED BIOREACTOR - KHOIRUNNISAA NIM: 21116025, FAIZAH
Laccase is an enzyme that can be used in a variety of biotechnological processes, such as the bioremediation of phenol pollutants, dye decolorization on textile waste, and pulp bleaching. This is because laccase has a wide substrate specificity, eco-friendly, and uses oxygen as the final electron acceptor. Laccase enzyme can be produced by white-rot fungi, i.e. Marasmius sp. by degrading lignin component of lignocellulose in agricultural waste, such as oil palm empty fruit bunches (OPEFB). Utilization of OPEFB can reduce enzyme production costs and answering high enzyme demand. Production of laccase enzyme by Marasmius sp. from OPEFB can be done using trickle-bed bioreactor with considering the aeration rate that may affect the growth and metabolic activity of Marasmius sp. The aim of study is to determine the optimum aeration rate (1,0; 1,5; and 2,0 vvm) in producing the highest activity of laccase using trickle-bed bioreactor. The enzyme production was performed using OPEFB with size of 1 cm and a temperature of 32Ã‚ÂºC for 14 days. During enzyme production, the Kirk medium (initial pH 4,5) was trickled continuously into the bioreactor at a rate of 10 mL/min and 1,5 liters of the medium was added on day 1 to 4, day 7, and day 10. The effluent is taken every 12 hours for measurement of enzyme activity: laccase, lignin peroxidase (LiP), manganese peroxidase (MnP), and cellulose using the spectrophotometric method. In addition; pH, lignin content, and reducing sugars were also measured. The results showed that the highest to the lowest laccase activity was produced respectively by the aeration rate of 1.5 vvm (36.66 U/mL at the 84th hour); 1.0 vvm (23.80 U/mL at the 180th hour); and 2.0 vvm (19.36 U/mL at the 84th hour). Other than laccase; the activity of cellulase, LiP, and MnP was detected; but their activity was lower than laccase. Based on these results, it can be concluded that the aeration rate can affect the laccase activity and the aeration rate of 1.5 vvm is the optimum rate for laccase production.